Bone Formation With the Combination of Simvastatin and Calcium Sulfate in Critical-Sized Rat Calvarial Defect - Myat Nyan; Daisuke Sato; Mitsumasa Oda; Tetsu Machida; Hiroshi Kobayashi; Takahiro Nakamura; Shohei Kasugai (Elsevier, 2007)
Simvastatin, a cholesterol synthesis inhibitor, enhances BMP2 expression in osteoblasts. The purpose of the present study was to examine whether simvastatin stimulates bone regeneration when combined with calcium sulfate as a carrier. Critical-sized bone defects in rat calvaria were treated with calcium sulfate or with combination of 1 mg simvastatin and calcium sulfate. In the combination group, although the least amount of bone formation with intense soft tissue inflammation was observed at 2 and 4 weeks, remarkable bone formation was evident at 8 weeks. Conclusively, the combination of simvastatin and calcium sulfate stimulated bone regeneration in spite of the inflammatory response. Keywords:: simvastatin, calcium sulfate, bone formation